2021
DOI: 10.3390/rs13245042
|View full text |Cite
|
Sign up to set email alerts
|

MDPrePost-Net: A Spatial-Spectral-Temporal Fully Convolutional Network for Mapping of Mangrove Degradation Affected by Hurricane Irma 2017 Using Sentinel-2 Data

Abstract: Mangroves are grown in intertidal zones along tropical and subtropical climate areas, which have many benefits for humans and ecosystems. The knowledge of mangrove conditions is essential to know the statuses of mangroves. Recently, satellite imagery has been widely used to generate mangrove and degradation mapping. Sentinel-2 is a volume of free satellite image data that has a temporal resolution of 5 days. When Hurricane Irma hit the southwest Florida coastal zone in 2017, it caused mangrove degradation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The total mangrove loss rate per year between 2016 and 2022 in the study area is -1.506% which mean the mangrove area in the study location has declined. The mangrove forest loss is likely due to hurricane event that happened in the study area as reported in the previous research 18,21 . Based on this result, the U-Net model successfully used here foe mangrove mapping and monitoring and achieved good results.…”
Section: Evaluation Assessmentssupporting
confidence: 57%
See 3 more Smart Citations
“…The total mangrove loss rate per year between 2016 and 2022 in the study area is -1.506% which mean the mangrove area in the study location has declined. The mangrove forest loss is likely due to hurricane event that happened in the study area as reported in the previous research 18,21 . Based on this result, the U-Net model successfully used here foe mangrove mapping and monitoring and achieved good results.…”
Section: Evaluation Assessmentssupporting
confidence: 57%
“…This study not use all the Sentinel-2 bands, we selected some Sentinel-2 bands and produced four spectral indices that useful for mangrove mapping as the input data based on previous research 18 . The total input bands for this study are 10 bands included blue, green, red, NIR, SWIR-1, SWIR-2, normalized difference vegetation index (NDVI), combined mangrove index (CMRI), normalized difference mangrove index (NDMI), and modified mangrove recognition index (MMRI) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various deep-learning techniques have been developed to understand the condition of mangrove ecosystems. For example, Jamaluddin et al [41] used MDPrePost-Net to determine the extent of mangrove degradation caused by the impact of Hurricane Irma as well as training data of around 40 million pixels with Sentinel-2 images and achieved an overall accuracy of 99.44%. Lin et al [42] used Convex Deep Mangrove Mapping (CODE-MM) to map mangroves in several countries, along with Sentinel-2 images and training data of around 4-50 million pixels, to achieve an overall accuracy of 86.16-97.65%.…”
Section: Introductionmentioning
confidence: 99%